Gastrointestinal Malignancies A Practical Guide on Treatment Techniques (Practical Guides in Radiation Oncology, 2018)
This book is a practical guide on how best to incorporate advanced radiation therapy techniques into the multimodality treatment of a wide range of gastrointestinal tumors, including esophageal cancer, gastric cancer, hepatobiliary malignancies (primary and metastatic liver tumors, intrahepatic, perihilar, and extrahepatic cholangiocarcinomas, and gallbladder cancer), pancreatic cancer, colorectal cancer, and carcinoma of the anal canal. Practical considerations when treating patients with external beam radiation therapy, intensity-modulated radiation therapy, particle therapy, and stereotactic body radiation therapy are clearly explained. Detailed attention is devoted to the safety and efficacy of radiotherapy in combination with current and emerging systemic therapies (chemotherapy, immunotherapy, and biologic agents), surgery, and ablative therapy, and the advantages and disadvantages of alternative treatment approaches for different tumor types are carefully evaluated. The book will benefit radiation oncologists, medical and surgical oncologists, medical physicists, medical dosimetrists, and other oncology professionals.